REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN VIDEO ANIMASI FLASH TENTANG GRAVITASI DI SMA - Muharrifa, Nur Riqqah; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to know the effectiveness of the use of flash animation video to remediation students misonception on the matter of gravity. The from of research used is pre-experimental designs with type one-group pretest-posttest design. A total 21 students from class XI IPA 2 SMA Negeri 1 Sanggau become sample of selected research by using intact group random sampling. Diagnostic tests consisting of questions in the from of two-tier multiple choice was used as a research instrument to know the conception of students. Based on the results of the analysis obtained the precentage of average students who experienced misconceptions before and after learning of 47,62% and 26,19% with an average decrease in misconceptions of 21%. Besed on the Wilcoxon test results obtained a value so it can be said there is a decrease in the percentage of students who suffered a significant misconception using flash animation video on the matter of gravity. The great effectiveness of the use of flash animation video in the remediation of students misconception is high (). Thus it can be concluded that the use of flash animation video is effective in remediating students misconception on the matter of gravity. This research is expected to be used as a reference for the teachers to remediate students misconception. Keywords : Remediation, Flash Animation Video, Misconception, Gravity